1988
DOI: 10.1111/j.1600-0714.1988.tb01520.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical staining for vimentin filaments and S‐100 protein in myxoma of the jaws

Abstract: Two jaw myxomas have been analyzed by a panel of antibodies to characterize this tumour type. Vimentin, but not keratin, neuron‐specific enolase (NSE), glial fibrillary acidic protein (GFAP), neurofilament (NF), desmin and Factor VIII‐related antigen (FVIII‐AG), demonstrated positivity in the cytoplasm of the neoplastic cells. Moreover, an antibody against S‐100 protein also showed a strong positive reaction in the cytoplasm of the tumour cells examined. Thus directly indicating a mesenchymal derivation for od… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0
7

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 18 publications
0
9
0
7
Order By: Relevance
“…16 Positivity for S-100 protein staining, neuronespecific enolase and factor VIII-related protein antigen have been described in the tumour cells. 17 Immunohistochemistry was unhelpful in our case because smooth muscle markers and S-100 protein were negative.…”
Section: Figmentioning
confidence: 72%
“…16 Positivity for S-100 protein staining, neuronespecific enolase and factor VIII-related protein antigen have been described in the tumour cells. 17 Immunohistochemistry was unhelpful in our case because smooth muscle markers and S-100 protein were negative.…”
Section: Figmentioning
confidence: 72%
“…17 Our findings are, to some extent, comparable with those previously obtained in odontogenic myxoma of the jaw, where myxoma cells are immunoreactive with antibodies against VIM and S100, but not with those against desmin and cytokeratin. 18,19 Intramuscular, juxta-articular and cutaneous myxoma cells consistently express VIM, although they rarely stain for S100. Furthermore, variable immunohistochemical expression of SMA, MSA, desmin and CD34 has been observed in myxomas of other locations.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there has been only one immunohistochemical study in odontogenic myxoma. More recently, LoMBARDi et al (14) reported the demonstration of S-100 protein and vimentin. Our aim was to examine the pattern of expression of the mesenchymal markers, to better define this neoplasm.…”
mentioning
confidence: 98%